Trends characterizing technological innovations that increase environmental pressure: A typology to support action for sustainable consumption - Lefèvre, Thierry; Déméné, Claudia; Arpin, Marie-Luc; Elzein, Hassana; Genois-Lefrançois, Philippe; Morin, Jean-François; Cheriet, Mohamed (Frontiers in Sustainability, 2022)
Technological innovation is widely recognized as an endogenous element of capitalism driving economic growth and consumption. Although technological innovations have benefited human health, quality of life, and comfort, especially in high-income countries, uncontrolled industrialization of technological innovations and mass consumption exert strong environmental pressure on natural resources and contribute to the degradation of the environment. Apart from their endogenous role in economy and consumption, these innovations are characterized by specific trends that affect the sustainability of manufactured goods and consumption patterns, such as rate of market penetration, ownership of manufactured goods, product lifespan, reparability, and recyclability. This paper aims to contribute to a theorization of the relationship between technological innovation, consumption, and sustainability. To this end, we propose a typology of trends characterizing technological innovation to constitute a coherent framework. These trends are then documented to evaluate their magnitude, drivers, and related issues, following the broad principles of integrative literature reviews through a purposeful review sampling. The following trend framework emerged with regards to technological innovations: (a) accumulation; (b) diversification; (c) substitution; (d) complexification. The work contributes to identifying and formalizing: (1) the terminology regarding each trend, (2) related concepts that should be considered to theorize the relationship between technological innovation and (un)sustainable consumption patterns, (3) the main drivers that sustain these trends, (4) interactions between these trends, and (5) societal consequences on material and energy consumption and waste management.